Multiplying and Dividing Radical Expressions

Multiplying and dividing radical expressions above fold leftMultiplying and dividing radical expressions above fold right
HomeAlgebraRadicals

Radical Expressions are math operations having multiple terms.

Radical Multiplication

√2(√18 + √6) = √36 + √12 = √( 6 • 6) + √(2 • 2 • 3) = 6 + 2√3

The FOIL Method (First-Outer-Inner-Last):

(2 + √3) (4 - 3√3) =

F = 2 • 4 = +8

O = 2 •∙ (-3√3) = -6√3

I = √3  • 4 = 4√3

L = √3  • (-3√3) = -3 • 3 = -9

8 - 6√3 + 4√3 - 9 = -1- 2√3

Radical Multiplication Math Example:

x2 + 8x + 13 when x = -4 + √3

(First, substitute “x” with -4 + √3)

(-4 + √3) 2 + 8(-4 + √3) + 13 =

(Next, remove square from expression)

[(-4 + √ 3) (-4 + √3)] + (-32 + 8√3  ) + 13 =

[ 16 - 4√3 - 4√3 + 3 ] - 32 + 8√3 + 13 = 16 - 8√3 + 3 - 32 + 8√3 + 13 =

16 + 3 - 32 + 13 - 8√3 + 8√3 = 0

Radicals Division by Rationalizing Denominators

Radical denominators having two or more terms:

(4 + 2√5 ) / (5 - √5)

First, remove Radicals from denominator using the conjugate 5 + √5

(4 + 2√5) (5 + √5) ÷ (5 - √5) (5 + √5) =

(20 + 4√5 + 10√5 + 10) ÷ (25 + 5√5 - 5√5 - 5) =

30 + 14√5 ÷ 20 = (15 + 7√5) / 10

Radical denominators that divide all terms of numerator:

(√32 + √24 - 3√6) ÷ √2 =

First, divide all terms by denominator √2 to remove radical from denominator.

[(√32 + √24 - 3√6) / √2] ÷ [√2 / √2] =

(√16 + √12 - 3√3) / 1 =

4 + 2√3 - 3√3 =

4 - √3

Top of Page

Copyright © DigitMath.com

All Rights Reserved.

AboutPrivacy